2007
DOI: 10.1007/bf02685923
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cadmium and zinc on the quality of quail's eggs

Abstract: We report the effects of cadmium (Cd) and zinc (Zn) on the quality of Japanese quail's eggs. For this study, 60 birds were divided into 3 groups of 20 subjects each. The animals in group 1 received 4 mg Zn/d, whereas those in group 2 were given a combination of 4 mg Zn/d and 0.12 mg Cd/d. The quails in group 3 were not given any supplements, acting as controls. The distribution of Cd and Zn in the eggs, the eggs' mass, and the strength and thickness of the shells were determined after 35 and 58 d of supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 5 publications
2
9
1
Order By: Relevance
“…Reference values for breaking strength are not mentioned in the current OECD guideline but our findings appear reliable since they were in the same range as those found in the older literature (Eroschenko and Place, 1977;Hartner and von Faber, 1980;Biessmann, 1982). More recently, after completion of our studies, Korénekova et al (2007) measured in two separate groups of untreated Japanese quail a mean eggshell breaking strength of 12.1 ( + 2.0) and 13.1 ( + 1.4) N, respectively. Kamata et al (2006aKamata et al ( , 2006bKamata et al ( , 2009 reported mean values between 10.42 and 13.08 N for their different experiments proving a rather high variability of this parameter.…”
Section: Introductionsupporting
confidence: 81%
“…Reference values for breaking strength are not mentioned in the current OECD guideline but our findings appear reliable since they were in the same range as those found in the older literature (Eroschenko and Place, 1977;Hartner and von Faber, 1980;Biessmann, 1982). More recently, after completion of our studies, Korénekova et al (2007) measured in two separate groups of untreated Japanese quail a mean eggshell breaking strength of 12.1 ( + 2.0) and 13.1 ( + 1.4) N, respectively. Kamata et al (2006aKamata et al ( , 2006bKamata et al ( , 2009 reported mean values between 10.42 and 13.08 N for their different experiments proving a rather high variability of this parameter.…”
Section: Introductionsupporting
confidence: 81%
“…The ubiquitous nature of Cd poses a hazard to humans and farm animals, since they are exposed to this heavy metal through the food supply and as a result it is accumulated in the body (Anetor, 2012; Bernard, 2008; Clemens et al, 2013; Kar & Patra, 2021; Rani et al, 2014; Schaefer et al, 2020; Shimada et al, 2008). Although acute exposure ofCd is unlikely in most commercial production systems, chronic Cd exposure, even at very low doses, can decrease growth, increase feed conversion ratio (FCR) and impair both egg production and egg quality (Koréneková et al, 2007; Swapna et al, 2010). As reviewed by Kar and Patra (2021), Cd accumulation in birds occurs mainly in the liver (bound with metallothionein) and kidney (for excretion).…”
Section: Introductionmentioning
confidence: 99%
“…Also, Zn can participate in energy regulation, lipid metabolism, protein degradation and synthesis (Attia, Abd Al-Hamid, ElKomy, et al 2013;Muralisankar et al 2014). Japanese quails are relatively susceptible to Zn deficiency, compared to other poultry species, and it is known that 25-50 mg Zn/kg of feed is normally required for the rearing of quails in standard circumstances (Korenekova et al 2007).…”
Section: Introductionmentioning
confidence: 99%